(untitled) (Research, Society and Development, 2020)
In the fermentation process, yeasts need to adapt to the environmental changes that occur during the production process. Responses to these adjustments can alter biochemical routes and the amount of metabolites produced. Thus, the objective was to analyze the fermentative parameters of industrial yeast strains in different growing conditions, as well as to evaluate the its applicability in different sectors of goods and services. A pre-inoculum was performed with the YPSAC 5% medium for the activation of the yeasts Catanduva-1 and Fleischmann that remained incubated for 24 hours at 30 °C at 250 rpm. After the cells were recovered by centrifugation and inoculated in the fermentation medium based on sugarcane juice at 15 °Brix at temperatures of 30 and 40 °C. Aliquots were removed for the analysis of the fermentative parameters. Concomitantly, a survey was carried out regarding the use of yeasts in the process of preparing goods and services. The data show that the best yeast fermentation performance occurred at 30 °C in 10 hours. In addition, yeasts have the ability to produce, under ideal conditions, metabolites that can be used in different biotechnological processes.